The FOCUS-PDCA can effectively optimize the critical value of test items: FOCUS-PDCA can effectively optimize the critical value of test items - Xie, Chunbao (Journal of Medical Biochemistry, 2022)
Objective: To optimize the critical value of test items using FOCUS-PDCA (ﬁnd, organize, clarify, understand, select, plan, do, check and act), and to set the personalized critical value of the test for different departments.Methods: We searched for literature reporting on the critical value and FOCUS-PDCA published over recent 5 years in order to understand the significance and status quo of critical value and FOCUS-PDCA. We also collected and analyzed the critical value data of hospital tests performed in Sichuan province hospitals in 2019, which were later compared to data from 2020 to determine the FOCUS-PDCA cycle.Results: The proportion of critical values in the whole hospital decreased from 3.5% before optimization to 2.5% to 3% after optimization. The critical values of ICU, hematology, nephrology, urology, and neonatal departments after optimization significantly decreased compared with those before optimization, while the critical values of cardiac surgery, emergency ICU, cardiology, and neurosurgery ICU showed no significant difference before and after optimization. Contrary, the critical values of the infection department after optimization significantly increased before optimization.Conclusion: FOCUS-PDCA can effectively optimize the critical value of test items, which is beneficial for rational utilization of medical resources.
Keywords: Critical Value; Optimization; FOCUS-PDCA